Assessment of the antidiabetic potential of extract and novel phytoniosomes formulation of Tradescantia pallida leaves in the alloxan‐induced diabetic mouse model. Issue 4 (1st March 2023) - Imtiaz, Fariha; Islam, Muhammad; Saeed, Hamid; Ahmed, Abrar; Rathore, Hassaan Anwer
Abstract: Diabetes inflicts health and economic burdens on communities and the present antidiabetic therapies have several drawbacks. Tradescantia pallida leaves have been used as a food colorant and food preservative; however, to our knowledge antidiabetic potential of the leaves of T. pallida has not been explored yet. The current study aimed to investigate the antidiabetic potential of T. pallida leaves extract and its comparison with the novel nisosome formulation of the extract. The leaves extract and phytoniosomes of T. pallida in doses of 15, 25 and 50 mg/kg were used to assess the oral glucose loaded, and alloxan‐induced diabetic mice models. The biological parameters evaluated were; change in body weight, blood biochemistry, relative organ to body weight ratio and histopathology of the liver, pancreas and kidney. Results revealed that the extract 50 mg/kg and phytoniosomes 25 and 50 mg/kg remarkably reduced the blood glucose level in all hyperglycemic mice by possibly inhibiting α‐amylase and α‐glucosidase production. Body weight and blood biochemical parameters were considerably improved in phytoniosomes 50 mg/kg treated group. The relative body weight was similar to those of healthy mice in extract 50 mg/kg, phytoniosomes 25 mg/kg, and phytoniosomes 50 mg/kg treated groups. Histopathology showed the regeneration of cells in the CHN50 treated group. Hyphenated chromatographic analysis revealed potent metabolites, which confirmed the antidiabetic potential of the extract by inhibiting α‐amylase and α‐glucosidase using in silico analysis. The present data suggested that phytoniosomes have shown better antidiabetic potential than crude extract of these leaves. Abstract : The graphical abstract depicts the potential of novel phytoniosomes formulation in comparison with the parent extract. The antidiabetic potential of the extract and phytoniosomes was checked by monitoring blood glucose level for 28 days by employing mice models. After 28 days, blood biochemical test and histopathological analysis revealed remarkable antidiabetic potential of phytoniosomes when compared with standard and extract. The mechanism of action and drug‐likeness of the putative compounds responsible for antidiabetic activity was validated using in silico models.